Peningkatan Kemampuan Guru Dalam Menulis Karya Ilmiah Melalui Kegiatan Pengabdian Pada Masyarakat - Fikrah Waruwu; Hardin Ade Ridwan Waruwu (CV. SINAR HOWUHOWU, 2024)
One aspect of teacher professionalism involves scientific article writing skills. The purpose of this community service program is to improve teachers' scientific writing skills and competencies. This community service is planned for three months, with implementation methods including 1) discussion with the community, and 2) writing practice with the community. The evaluation of the activity showed good success and in accordance with expectations, reflected in the enthusiasm of teachers in participating in the entire training, both in providing material to the community and direct practice in writing scientific papers. Before the training, only 7 teachers had the potential to write scientific papers well, but after doing this service activity, there were about 20 teachers who could compile or make scientific papers, and there were about 5 teachers who were still constrained. And the quality of the article is quite good.